A feeling for books : the Book-of-the-Month Club, literary taste, and middle-class desire - Radway, Janice A., 1949- (Chapel Hill : University of North Carolina Press, 1950)
A Feeling for Books is at once a fascinating study of an influential cultural institution and a profoundly personal meditation on the love of books and the experience of reading. Deftly melding cultural history, literary criticism, and autobiographical reflection, Janice Radway traces the history of the Book-of-the-Month Club from its controversial founding in 1926 through its evolution into an organization uniquely successful in blending commerce and culture. Working, as an ethnographer would, from interviews with club employees and with records left by the club's founders and original judges, Radway reconstructs the standards and ethos as well as the tastes and passions that drove club officials. In the process, she provides an insightful look at the attractions of middlebrow culture and an intriguing account of middle-class Americans' desire to display the tasteful signs of learning and education.
Pt. I. In the Service of the General Reader. Ch. 1. A Certain Book Club Culture. Ch. 2. A Business with a Mission. Ch. 3. The Intelligent Generalist and the Uses of Reading -- Pt. II. On the History of the Middlebrow. Ch. 4. The Struggle over the Book, 1870-1920. Ch. 5. A Modern Selling Machine for Books: Harry Scherman and the Origins of the Book-of-the-Month Club. Ch. 6. Automated Book Distribution and the Negative Option: Agency and Choice in a Standardized World. Ch. 7. The Scandal of the Middlebrow: The Professional-Managerial Class and the Exercise of Authority in the Literary Field. Ch. 8. Reading for a New Class: The Judges, the Practical Logic of Book Selection, and the Question of Middlebrow Style -- Pt. III. Books for Professionals. Ch. 9. A Library of Books for the Aspiring Professional: Some Effects of Middlebrow Reading.
Includes bibliographical references (p. [397]-410) and index.
Keywords: Book-of-the-Month Club -- History; Books and reading -- United States -- History -- 19th century; Books and reading -- United States -- History -- 20th century; Popular culture -- United States -- History -- 19th century; Popular culture -- United States -- History -- 20th century